Effect of Fluoride on Cytotoxicity Involved in Mitochondrial Dysfunction: A Review of Mechanism - Wei, Mingbang; Ye, Yourong; Ali, Muhammad Muddassir; Chamba, Yangzom; Tang, Jia; Shang, Peng (Frontiers in Veterinary Science, 2022)
Fluoride is commonly found in the soil and water environment and may act as chronic poison. A large amount of fluoride deposition causes serious harm to the ecological environment and human health. Mitochondrial dysfunction is a shared feature of fluorosis, and numerous studies reported this phenomenon in different model systems. More and more evidence shows that the functions of mitochondria play an extremely influential role in the organs and tissues after fluorosis. Fluoride invades into cells and mainly damages mitochondria, resulting in decreased activity of mitochondrial related enzymes, weakening of protein expression, damage of respiratory chain, excessive fission, disturbance of fusion, disorder of calcium regulation, resulting in the decrease of intracellular ATP and the accumulation of ROS. At the same time, the decrease of mitochondrial membrane potential leads to the release of Cyt c, causing a series of caspase cascade reactions and resulting in apoptosis. This article mainly reviews the mechanism of cytotoxicity related to mitochondrial dysfunction after fluorosis. A series of mitochondrial dysfunction caused by fluorosis, such as mitochondrial dynamics, mitochondrial ROS, mitochondrial fission, mitochondrial respiratory chain, mitochondrial autophagy apoptosis, mitochondrial fusion disturbance, mitochondrial calcium regulation are emphasized, and the mechanism of the effect of fluoride on cytotoxicity related to mitochondrial dysfunction are further explored.